2015
DOI: 10.1007/s40870-015-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Collapse of a Cylindrical Pore in the Energetic Material α-RDX

Abstract: Molecular dynamics simulations were used to study the shock-induced collapse of cylindrical pores in oriented single crystals of the energetic material a-1,3,5-trinitroperhydro-1,3,5-triazine (a-RDX). The shock propagation direction was parallel to the [100] crystal direction and the cylinder axis of the initially 35.0 nm diameter pore was parallel to [010]. Features of the collapse were studied for Rankine-Hugoniot shock pressures P s = 9.71, 24.00, and 42.48 GPa. Pore collapse for the weak shock is dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 72 publications
2
41
2
Order By: Relevance
“…The vortical flow ‘rolls up’ the hotspot in the regions of the sidelobes. While this rollup and concentration of the high temperatures in the vortex cores have been observed in MD calculations as well , in the present study the strong anisotropy appears to disrupt the formation of concentrated vortical structures. Despite these differences, the overall locations of the incident shock wave, the blast wave emanating from the collapse site, and the location of the Mach stem and triple points all appear to be in fairly good agreement between the MD and continuum predictions.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The vortical flow ‘rolls up’ the hotspot in the regions of the sidelobes. While this rollup and concentration of the high temperatures in the vortex cores have been observed in MD calculations as well , in the present study the strong anisotropy appears to disrupt the formation of concentrated vortical structures. Despite these differences, the overall locations of the incident shock wave, the blast wave emanating from the collapse site, and the location of the Mach stem and triple points all appear to be in fairly good agreement between the MD and continuum predictions.…”
Section: Resultssupporting
confidence: 74%
“…Specific equations used to compute the various other properties used for the MD analysis are described elsewhere [72][73][74][75].…”
Section: Trajectory Analysismentioning
confidence: 99%
“…The journal is highly international, publishing experimental and theoretical studies of metals [57], polymers [58], glasses [59], composites [60], granular materials [61], explosives [62], biological materials [63], geological materials [64], phase transitions [65], and structural response [66]. The journal includes application and development of techniques including split Hopkinson pressure bar/Kolsky bar [67], plate impact with light gas guns and powder guns [68], Taylor Anvil [69], Dynamic-TensileExtrusion [70], spectroscopy-and pyrometry-based shock temperature measurements [71], optical and X-ray imaging methods [72], interferometry and velocimetry techniques [73], dynamic fracture [74], laser based dynamic drivers [75], penetration and ballistics [76], equation of state [77], and spall failure [78].…”
Section: Members Of the Photoelasticity Conference And Guestsmentioning
confidence: 99%
“…It has been suggested that the pore collapse (e. g., the viscoplastic deformation, the hydrodynamic micro jetting, the compression of gas in cavities and the shear bandings) is a dominant hot-spot generation mechanism for the shock initiation in pressed solid explosives [6][7][8][9][10]. Numerous researches have investigated the pore collapse hot-spot ignition mechanism via experiments (the voids in mm-scale) [11][12][13], molecular dynamics (MD) simulations [14,15] and mesoscale simulations [16,17], suggesting that the initial size and shape of the pore, the material viscosity, and the shock pressure have noticeable effects on the hot spot formation. These studies have permitted a closer micro-mechanical description and accurate prediction of the pore collapse hot spot formation mechanisms.…”
Section: Introductionmentioning
confidence: 99%